Opsoclonus-Myoclonus Following Mycoplasma Pneumoniae Infection - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Three adolescent cases of opsoclonus-myoclonus (OMS) that followed infection with mycoplasma pneumoniae are reported from University Hospital, Bern, Switzerland.